Multidrug Resistant Tuberculosis With Simultaneously Acquired Drug Resistance to Bedaquiline and Delamanid. (30th July 2020) - Yoshiyama, Takashi; Takaki, Akiko; Aono, Akio; Mitarai, Satoshi; Okumura, Masao; Ohta, Ken; Kato, Seiya
Abstract: This study is the first to report a clinical case of simultaneously acquired resistance to bedaquiline (BDQ) and delamanid (DLM). Whole genome sequencing revealed 2 nucleotide insertions (Rv0678 and fbiC) in the Mycobacterium tuberculosis isolate. The minimum inhibitory concentrations for BDQ and DLM were 0.25 µg/mL and >2.0 µg/mL, respectively.